PROFIL PEMECAHAN MASALAH ETNOMATEMATIKA PADA MATERI GEOMETRI BAGI SISWA BERKEMAMPUAN MATEMATIKA TINGGI - Selviani, Mini Tika; Rasiman, Rasiman; Pramasdyahsari, Agnita Siska (Universitas Insan Budi Utomo, 2021)
This study aims to determine the profile of ethnomathematics problem solving in geometry material in terms of students’ mathematical abilities. This type of research is a descriptive qualitative research. The subject taken were one class VIII student who had high mathematical abilities. Data collection was carried out by means of a math ability test, ethnomathematics problem solving test, and interviews. The data analysis technique was carried out in three stages, namely reduction, presentation, and drawing conslusions. The validity of the data used triangulation method, which is to compare the results of ethnomathematics problem solving tests with the results of interviews. The analysis was developed based on indicators of problem-solving abilities with attention to students’ mathematical abilities. Based on the results of the analysis, ethnomathematics can improve mathematical skills which have an impact on increasing the problem-solving abilities of students. Ethnomathematics based problem solving in geometry material makes it easier for students to express student’s mathematical knowledge and skills. It is proven that subjects with high mathematical abilities also have high problem solving abilities.